2009
DOI: 10.1108/13527600910953928
|View full text |Cite
|
Sign up to set email alerts
|

Person/organization job‐fitting and affective commitment to the organization

Abstract: Purpose -The aim of this paper is to examine the mediation effect of the psychological contract (PC) on the relationship between person-organization (P-O) fit, person-job (P-J) fit and affective commitment to the organization (organizational affective commitment or OAC). Design/methodology/approach -The empirical data for the study were collected using selfadministered questionnaires with 960 participants from 16 large companies in the UAE. Respondents were asked to provide their perceptions of the main concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 70 publications
2
27
0
2
Order By: Relevance
“…To understand the issue of increasing unemployment of UAE nationals, the relationship between the characteristics of individuals, their jobs, and their organizations must be better understood and better aligned, because they are "related to both productivity and commitment" (Behery, 2009, p. 179). Behery (2009) describes the person-organization fit and the personjob fit that can be obstacles in hiring practices in private sector companies because "many organizations are yet to discover the link between investing in people and work outcomes such as customer satisfaction, high work performance, and profit" (p. 180). Organizations, especially in the private sector, "should continue to look at their socialization tactics to enhance the organizational commitment among their employees," whether Emirati or expatriate (Behery, 2009, p. 191).…”
Section: Social Transitions Resulting From Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the issue of increasing unemployment of UAE nationals, the relationship between the characteristics of individuals, their jobs, and their organizations must be better understood and better aligned, because they are "related to both productivity and commitment" (Behery, 2009, p. 179). Behery (2009) describes the person-organization fit and the personjob fit that can be obstacles in hiring practices in private sector companies because "many organizations are yet to discover the link between investing in people and work outcomes such as customer satisfaction, high work performance, and profit" (p. 180). Organizations, especially in the private sector, "should continue to look at their socialization tactics to enhance the organizational commitment among their employees," whether Emirati or expatriate (Behery, 2009, p. 191).…”
Section: Social Transitions Resulting From Developmentmentioning
confidence: 99%
“…Other studies conducted by the Federal Authority for Government Human Resources (FAGHR) (UAE Government, 2011) and researchers (Elamin, 2011;Shallal, 2011) found Emirati women vastly preferred working in the public sector because the shorter working hours allowed for more of a home-work life balance because Emirati women, even those with full-time jobs, shoulder most of the domestic responsibilities in Emirati social structure. Private sector vacancies are quickly filled by qualified and experienced foreign laborers who are willing to work longer hours for less compensation than their Emirati counterparts (Behery, 2009). Daleure and Al Shareef (2015) found that Emirati dissatisfaction with the private sector is not likely to improve if the sector remains in its current state, since employers have little incentive to make workplaces more attractive to Emiratis or to make retaining Emiratis a corporate priority.…”
Section: Introductionmentioning
confidence: 99%
“…A good fit creates good behavior [10,12,19]. A good P-E fit, for example, reduces workplace conflict [20], boosts employee motivation, and increases their commitment [21]. In this situation, employees tend to be satisfied with their job and have best chances of career success [22].…”
Section: Person-job Fitmentioning
confidence: 99%
“…Similarly, studies on person-job fit were limited to those that were done in abroad (e.g. Caldwell & O'Reilly, 1990;Carless, 2005); Hecht & Alle, 2003;Erdogan & Bauer, 2005;Behery, 2009). Given the importance of both employees' job performance and the service SMEs in Malaysia, the aim of this research is to ascertain whether employee competency and person-job fit is significantly related to the employee's job performance.…”
Section: Gaps In the Literaturementioning
confidence: 99%